Mussel‐inspired bio‐based water‐resistant soy adhesives with low‐cost dopamine analogue‐modified silkworm silk Fiber. Issue 23 (9th December 2019) - Pang, Huiwen; Zhao, Shujun; Mo, Liuting; Wang, Zhong; Zhang, Wei; Huang, Anmin; Zhang, Shifeng; Li, Jianzhang
ABSTRACT: Mussel‐inspired dopamine chemistry is popular among engineers for surface modification on various substrates due to its high efficiency, handy operation process, and strong reactivity. However, the high cost of dopamine does not allow for mass production. In the present study, low‐cost dopamine analogues (alkali lignin and tannic acid) were used to fabricate high‐reactivity silkworm silk fiber (SF) via a simple dip‐coating approach, and were then applied to a soy‐based adhesive to enhance its performance. The SF tightly combines with soy protein mainly via a Schiff base reaction between polydopamine or dopamine analogue and the amine or thiol groups of soy protein; this forms a multiple crosslinked system and "reinforced concrete"‐like structure, as confirmed by Fourier transform infrared spectroscopy, X‐ray diffraction, thermogravimetry, and scanning electron microscopy analyses. As expected, the toughness of the soy‐based adhesive obviously improved and the highest wet shear strength of the adhesive samples attained 1.50 MPa, which is far greater than relevant interior use requirements. Though dopamine‐coated SF could significantly enhance the wet shear strength of the soy‐based adhesive by 387.1% compared to the pristine SM adhesive, lignin‐coated and tannic acid‐coated SFs are more suitable for practical application due to the lower cost of raw materials. The results of this study may represent an effective and low‐cost approach to mussel‐inspired surface modification chemistry for the mass production of high‐performance soy‐based adhesives. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48785. Abstract : Soy protein adhesive enhanced by dopamine analogue‐modified silkworm silk fiber